Capital Market School Matter? Empirical Evidence University Students in West Java - Gina Sakinah; Ade Ponirah; M Taufik Ridho; Taufik Ridwan Murthado; Tria Regina Fauzia (MAKSIMUM: Media Akuntansi Universitas Muhammadiyah Semarang, 2026)
This study analyzes university students' investment interest, minimum capital policy, investment knowledge, and the Technology advances of capital market school mediation effect, using a case study of university students in West Java. This study used the Theory of Planned Behavior (TPB) model approach. The data collection method was a questionnaire survey via Google Forms. The population surveyed in this study was all university students in West Java whose universities have an Investment Gallery. Meanwhile, the sample in this study was determined using a non-probabilistic selection technique known as purposive sampling. This study uses the Partial Least Squares Structural Equation Modeling technique to test the hypothesis. The survey results show that the minimum capital policy has a Significant Effect on the Minimum Capital Policy. Second, investment knowledge has a significant effect on investment interest. Third, technological advances have a substantial impact on investment interest. Fourth, capital market schools have a considerable impact on investment interest. The mediating variable of capital market schools cannot indirectly influence minimum capital policy, investment knowledge, and Technology advances regarding investment interest.